2003
DOI: 10.1097/00001813-200302000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Increasing-dose gemcitabine plus low-dose cisplatin in metastatic non-small cell lung cancer

Abstract: cisplatin 50 mg/m2 on day 1, gemcitabine starting at 1400 mg/m on days 1 and 8 every 21 days. Subsequent levels were increased by 200 mg/m2. Forty-two patients with metastatic NSCLC were enrolled (37 males; median age 61 years; squamous cell carcinoma 19 patients; performance status 2, in 13 patients; 18 patients had significant weight loss). MTD was found to be 2600 mg/m2 because of DLT in three of six patients: two neutropenic fever and one massive bleeding. Overall toxicity was generally mild consisting mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Gemcitabine and cisplatin are usually administered in combination to treat a variety of malignancies, such as in the treatment of non-small cell lung carcinoma 10 11. This doublet-based combination treatment may induce vascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine and cisplatin are usually administered in combination to treat a variety of malignancies, such as in the treatment of non-small cell lung carcinoma 10 11. This doublet-based combination treatment may induce vascular events.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Cisplatin, a platinum-containing agent, and gemcitabine, a pyrimidine nucleoside antimetabolite, are usually administered in combination to treat a variety of malignancies and appear to be most active in the treatment of non-small cell lung cancer. [2,3] Hitherto hepatic, cutaneous, and ocular veno-occlusive diseases, Raynaud's phenomenon, myocardial infarction, cerebral ischemia, thrombotic microangiopathy, hemolytic-uremic syndrome, arterial distal thrombosis, pulmonary embolism, iliac artery embolism, and deep venous thrombosis in upper and lower limbs have been reported with cisplatin and/or gemcitabine therapy. [1,4,5] A case of acute bilateral renal infarction in a patient with non-small cell lung carcinoma during chemotherapy with cisplatin and gemcitabine is reported here.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin and gemcitabine are usually administered in combination to treat a variety of malignancies, such as in the treatment of non-small cell lung carcinoma. [2,3] Cisplatin and gemcitabine treatment may induce vascular events. [1,4,5,11] It was shown that cisplatin increases platelet reactivity.…”
mentioning
confidence: 99%